Original Short Stories $1 (BVolume 10s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 10" by Guy de Maupassant is a collection of short stories written in the late 19th century. This volume contains a variety of narratives that explore themes of life, love, tragedy, and the human condition, often highlighting moments of intense emotion and moral complexity. The opening portion of this collection features a story titled "The Christening," which begins with a conversation between an old ship's surgeon and another character, reflecting on the destructive power of alcohol. The narrative follows a chilling incident surrounding a christening in Brittany, where traditions lead to the negligent exposure of a newborn to harsh winter conditions. The surgeon recounts how the child's father, Kerandec, and his family disregard the doctor's protests, adhering instead to their customs. Tragically, the story culminates in the death of the infant, revealing a grim commentary on societal norms and parental responsibility. (This is an automatically generated summary.)s
The christening -- The farmer's wife -- The devil -- The snipe -- The will -- Walter Schnaff's adventure -- At sea -- Minuet -- The son -- That pig of a Morin -- Saint Anthony -- Lasting love -- Pierrot -- A Normandy joke -- Father Matthew.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English